An anthropomorphic pelvis phantom for MR-guided prostate interventions - Bauer, Dominik F.; Adlung, Anne; Brumer, Irène; Golla, Alena-Kathrin; Russ, Tom; Oelschlegel, Eva; Tollens, Fabian; Clausen, Sven; Aumüller, Philipp; Schad, Lothar R.; Nörenberg, Dominik; Zöllner, Frank G. (Magnetic resonance in medicine, 2022)
Purpose To design and manufacture a pelvis phantom for magnetic resonance (MR)-guided prostate interventions, such as MRGB (MR-guided biopsy) or brachytherapy seed placement. Methods The phantom was designed to mimic the human pelvis incorporating bones, bladder, prostate with four lesions, urethra, arteries, veins, and six lymph nodes embedded in ballistic gelatin. A hollow rectum enables transrectal access to the prostate. To demonstrate the feasibility of the phantom for minimal invasive MRI-guided interventions, a targeted inbore MRGB was performed. The needle probe was rectally inserted and guided using an MRI-compatible remote controlled manipulator (RCM). Results The presented pelvis phantom has realistic imaging properties for MR imaging (MRI), computed tomography (CT) and ultrasound (US). In the targeted inbore MRGB, a prostate lesion was successfully hit with an accuracy of 3.5 mm. The experiment demonstrates that the limited size of the rectum represents a realistic impairment for needle placements. Conclusion The phantom provides a valuable platform for evaluating the performance of MRGB systems. Interventionalists can use the phantom to learn how to deal with challenging situations, without risking harm to patients.